Development of lab-scale forward osmosis membrane bioreactor (FO-MBR) with draw solute regeneration for wastewater treatment - Parveen, F (2018)
The overall aim of the current work was to perform a practical, lab-scale study to examine the component parts and integrated operation of a continuous and feasible FOMBR-MD hybrid system, for the treatment and recycle of wastewater. This was achieved by comparison of the performance of a commercial Cellulose triacetate (CTA) FO membrane with that of a single layer nanofiltration (NF) membrane when used with novel and conventional draw solutions. Higher flux and a higher decline in flux were observed for simple inorganic draw solutions compared to higher molecular weight draw solutions e.g. for CTA FO membrane in an MBR configuration, the flux (5.3 LMH) and the percentage decline in flux (43%) were highest for NaCl and lower for SDS (2.3LMH and 14.2% respectively) in MBR configuration (AL-FS). The fluxes as well as RSTs were higher for the NF membrane in comparison to the CTA FO membrane. In the absence of a reconcentration system in place after 24 hours of operation, the highest RST was observed for NaCl (9.33 GMH) and the lowest for higher molecular weight draw solutes (Poly ethylene glycol butyl ether (PGBE): 1.2 GMH) for the CTA FO membrane. Similar results were observed in the NF membrane. In the toxicity test, B.subtilis was still able to grow at the highest draw solution concentration (0.5M). The highest percentage growth was observed for Na3PO4 (53% compared to that of the control) and the lowest growth was observed for SDS (16%), proving their non-toxicity even at such a higher concentration. For MD optimisation, a temperature difference of 15ºC was chosen with a low feed temperature of 35ºC and a permeate temperature of 20ºC. An increase in cross flow velocity (CFV) decreased the temperature and concentration polarization and increased the flux for MD. An optimum CFV of 0.17 m/s was selected. The MD feed concentration also affected the flux when all other conditions were similar; slightly lower fluxes for feed (which was the diluted draw solutions) with higher molecular weight solutes (Polydiallyldimethylammonium chloride (PDAC): 1.8 LMH) were observed than with lower molecular weight solutes (NaCl: 2.1 LMH). When MD was combined in a hybrid system with FO, steadier fluxes were observed for the FO compared to FO run on its own, and the RST was lower. Due to a higher FO flux, a more balanced system was achieved for NaCl compared to that of TEAB (Tetraethylammonium bromide) and PDAC. The FO-MD hybrid enabled pure water production and a non-volatile component rejection of nearly 99%. Cleaning tests were performed on the membranes which were employed throughout this study, using both acidic (2% HNO3 with 2% H3PO4) and basic (0.5 mM EDTA with 0.5g/L NaOH) cleaning solutions. Observation of SEM images of the membrane surfaces revealed that the low molecular weight (NaCl) and high molecular weight (PAC) draw solutes exhibited a lower residual fouling after cleaning than the medium molecular weight (TEAB) draw solute. The level of residual fouling also seemed consistent with earlier observations of flux decline. Apart from the case of the NaCl draw solute, acidic cleaning was generally more effective than basic cleaning for both sides of the FO membrane. The two cleaning methods were equally effective for the MD membrane active layer